2014
DOI: 10.1186/1475-2867-14-63
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of ribavirin in combination with interferon-α on renal cell carcinoma cell lines in vitro

Abstract: BackgroundRibavirin is an anti-viral drug; however, recent data suggest that it may also be effective in cancer therapy. This study investigated the effect of ribavirin alone or in combination with IFN-α on biological processes: proliferation, apoptosis, and migration of murine (Renca) and human renal carcinoma (RCC) cells (786–0) in vitro.MethodsRenca and 786–0 cells were treated with IFN-α, ribavirin, or a combination of IFN-α and ribavirin at varying concentrations. Cell proliferation was evaluated using CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…In addition, ribavirin at 40 and 80 μM decreased proliferation and viability in normal liver cells, and to a significantly lesser extent than in HCC cells (Figures A and B). This is similar to the previous findings that ribavirin at 100 μM does not cause significant toxicity in normal kidney cells . We next investigated whether ribavirin is able to enhance the efficacy of HCC chemotherapy drug doxorubicin.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, ribavirin at 40 and 80 μM decreased proliferation and viability in normal liver cells, and to a significantly lesser extent than in HCC cells (Figures A and B). This is similar to the previous findings that ribavirin at 100 μM does not cause significant toxicity in normal kidney cells . We next investigated whether ribavirin is able to enhance the efficacy of HCC chemotherapy drug doxorubicin.…”
Section: Resultssupporting
confidence: 89%
“…Importantly, the dose of ribavirin that is effective in inhibiting HCC growth is not toxic to mice (Figure A). The preferential toxicity of ribavirin on tumor over normal counterparts has also been reported . Our findings together with previous studies clearly demonstrate the preferential anti‐cancer activities of ribavirin in various cancers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Various environmental factors can modulate the motility of cancer cells and affect invasion capacity of these cells. Teng et al showed that antiviral drug ribavirin causes a considerable suppression of the migration of renal cell carcinoma cell lines [14]. Boyden chamber migration assay was performed to assess whether ACV affects MCF7 chemopolarised migration.…”
Section: Resultsmentioning
confidence: 99%
“…Another antiviral agent - ribavirin was also reported as an immune response inducer in the renal cell carcinoma lines through the downregulation of IL-10 expression and the upregulation of TGF-β expression [14]. The mechanisms by which ACV enables its anticancer effects might involve an enhanced immune response of the cancer cells and further study is required in this area.…”
Section: Discussionmentioning
confidence: 99%